A review of strategies to incorporate flexibility in higher education course designs - Lumbini Barua; Barbara B. Lockee (Springer, 2024)
Abstract While the movement for flexibility in higher education can be traced back to the first corresponding courses in the 18th century, the recent pandemic has led to an unprecedented demand for flexible learning, particularly in higher education settings. This review of the literature delves into the evolution of flexible course design and defines flexibility as a multifaceted concept encompassing time, place, content, pace, and pedagogy, with learner autonomy situated at the core. This review explores the key components of flexible course design, including both pedagogical and logistical aspects, and their implications for developing a learner-centered approach to enhancing engagement and motivation. By synthesizing the current literature, this review highlights strategies to incorporate flexibility in course design through content adaptation, pedagogical modifications, assessment diversification, and adjustments in time, place, and pace of course offerings and learning. This review underscores the significance of flexible course design in light of the rapidly diversified learner demographic and their changing needs emphasizing the necessity of further research on flexibility for building more empathetic and adaptable learning environments.